Employment relations in local government: Strategic choices and the case of Brent - Kessler, I; Coyle-Shapiro, J; Purcell, J (2000)
Systematically evaluates changes in people management in one case study, the London Borough of Brent, as the major arena for the regulation of employment government moves from the national to the authority level. Considers the impact of upstream decisions on mission, purpose and structure and of downstream decisions on employment relations. as they relate to the structure of the personnel function, the role of line mangers in personnel activities, the way staff are treated and the role of the unions, based upon a strategic choice model. Argues that there are, indeed strong linkages between Brent upstream decision to become a "competitive market" authority and devolve decision making to business units and the dimensions of employment relations distinguished. However, the consequence of the upstream-downstream relationship were not necessarily as intended by the Borough, with some of the results having highly dysfunctional consequences for the organization.